Descemet membrane endothelial keratoplasty with stromal rim (DMEK-S) in complicated patients - Studeny, Pavel; Veith, Miroslav; Krizova, Deli (Biomedical papers, 2019)
Purpose. To evaluate the outcomes of the hybrid technique of posterior lamellar keratoplasty (Descemets' membrane endothelial keratoplasty with stromal rim, DMEK-S) in eyes with multiple ocular pathologies. Methods: A retrospective case control study of the consecutive group of all eyes with combined ocular pathologies which underwent DMEK-S keratoplasty. We evaluated the number of pre- and post-operative complications; uncorrected distance visual acuity (UDVA); corrected distance visual acuity (CDVA) and endothelial cell density (ECD). The first group (Group 1 - 100 eyes) was compared to a control group of eyes (Group 2 - 145 eyes) without combined ocular pathologies, which were operated throughout the same time period. Comparisons were made in the 12th month of the follow-up. Results: Both the UDVA and the CDVA statistical values 12 months after the surgery were significantly better in Group 2. ECD was comparable in both groups. The number of complications during surgery was considerably higher in Group 1, where a certain type of complication occurred in 15 eyes (15%), while in Group 2 this complication occurred only in 9 eyes (6.2%). In Group 1 a slightly higher number of rebubbling cases (52% vs. 48.3%) occurred, as well as more than twice as many cases of primary graft failure (34% vs. 15.7%) compared to Group 2. Conclusion: DMEK-S - hybrid endothelial transplantation in complicated eyes in the evaluated group of patients led to a noticeable improvement of visual acuity. When compared to surgeries in uncomplicated eyes, DMEK-S results in a higher rate of postoperative complications, especially graft detachment and primary failure.
Keywords: DMEK-S; lamellar keratoplasty; endothelial dystrophy; endothelial transplantation